Dependability Assessment of the Railway Signalling Systems Based on the Stochastic Petri Nets Analysis - Boudnaya, Jaouad; Mkhida, Abdelhak; Bououlid Idrissi, Badr (International Journal of Intelligent Systems and Applications in Engineering, 2015)
In this article, we propose a methodology to evaluate the performances of the railway signalling systems in terms of the availability. Firstly, level crossings in Morocco are presented. Secondly, a railway signalling system ERTMS level 2 modelling is proposed .The human factor and network failures are also taken into account. Finally, this system performance evaluation is proposed in every state (nominal way of functioning, degraded mode, and failure mode).